2022
DOI: 10.3390/biomedinformatics2020019
|View full text |Cite
|
Sign up to set email alerts
|

Meal and Physical Activity Detection from Free-Living Data for Discovering Disturbance Patterns of Glucose Levels in People with Diabetes

Abstract: Objective: The interpretation of time series data collected in free-living has gained importance in chronic disease management. Some data are collected objectively from sensors and some are estimated and entered by the individual. In type 1 diabetes (T1D), blood glucose concentration (BGC) data measured by continuous glucose monitoring (CGM) systems and insulin doses administered can be used to detect the occurrences of meals and physical activities and generate the personal daily living patterns for use in au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…We have shown that when using the blood glucose data of real patients, we need additional features, such as the ones extracted from heart rate signals. The Logistic Regression, AdaBoost, Random Forest, and Multi-Layer Perceptron with the ReLU and Tanh activation function were found to be the best five models from our tests; they provide better or comparable results to those reported in similar studies, e.g., [ 61 , 62 , 63 , 64 ]. The other models require a post-processing of the predicted data to be more precise.…”
Section: Discussionsupporting
confidence: 68%
“…We have shown that when using the blood glucose data of real patients, we need additional features, such as the ones extracted from heart rate signals. The Logistic Regression, AdaBoost, Random Forest, and Multi-Layer Perceptron with the ReLU and Tanh activation function were found to be the best five models from our tests; they provide better or comparable results to those reported in similar studies, e.g., [ 61 , 62 , 63 , 64 ]. The other models require a post-processing of the predicted data to be more precise.…”
Section: Discussionsupporting
confidence: 68%
“…Advancements in pervasive computing have seen an increase in the interest of researchers in human activity recognition. Human activity recognition has numerous application areas, such as; elder healthcare, 1 child monitoring, 2 rehabilitation monitoring, and general well‐being, 3 among other areas. Generally, activity data can be collected using the vision‐based method or sensor‐based method.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods use information from behavioral meal patterns to confirm a meal occurrence (Cameron et al 2012;Villeneuve et al 2020). Lastly, classification algorithms have also been used to discern the meal events, such as logistic regression (Garcia-Tirado et al 2021c;Garcia-Tirado et al 2021b;Corbett et al 2022), linear discriminant analysis (Kölle et al 2017;Kölle et al 2020), extended isolation forest (Zheng et al 2020), fuzzy logic (Samadi et al 2017), or recursive neural networks (Askari et al 2022).…”
Section: Detection-based Meal Compensationmentioning
confidence: 99%
“…Food intake usually follows daily patterns (Askari et al 2022). Some predictionbased controllers, namely MPC, have exploited this property to enhance the prediction quality against unannounced meals and consequently improve the control performance.…”
Section: Meal Anticipation From Historical Datamentioning
confidence: 99%
See 1 more Smart Citation